Retinal arteriolar parameters as a surrogate marker of intracranial vascular pathology. Issue 1 (5th July 2022) - Abdelhak, Ahmed; Solomon, Isaac; Montes, Shivany Condor; Saias, Alexandra; Cordano, Christian; Asken, Breton; Fonseca, Corrina; Oertel, Frederike Cosima; Arfanakis, Konstantinos; Staffaroni, Adam M.; Kramer, Joel H.; Geschwind, Michael; et al.
Abstract: Introduction: Development of novel diagnostic tools is a top research priority in vascular dementia. A major obstacle is the lack of a simple, non‐invasive method to visualize cerebral arteriolar walls in vivo. Retinal arterioles offer a window into the cerebral circulation. Methods: I ntensity‐b ased r etinal a rteriolar v isualization in o ptical coherence tomography (I‐bRAVO) was applied to evaluate mean wall thickness (MWT) and wall‐to‐lumen ratio (WLR) in 250 subjects with sporadic and genetic cerebral small vessel disease (CSVD), non‐vascular neurodegenerative diseases (NVND), and healthy controls (HC) in association with imaging and cognitive markers. Results: MWT and WLR were higher in CSVD, associated with severity of vascular white matter lesions, and correlated with magnetic resonance imaging‐based intracranial arteriolosclerosis score. WLR correlated with gray and white matter volume and differentiated asymptomatic sporadic CSVD from HC (area under the curve = 0.82). Discussion: I‐bRAVO is a rapid, non‐invasive tool. MWT and WLR were associated with imaging markers of CSVD and could contribute to early identification of sporadic CSVD.